Nutritional intake and dietary knowledge of athletes: A scoping review - Hopper, C.; Mooney, E.; Mc Cloat, A. (Nutrients, 2025)
Background: Sports nutrition is a rapidly developing field of study, and optimum nutrition can have a crucial impact on athletic performance and, in turn, overall well-being. Nutritional knowledge and dietary intake of athletes are paramount in terms of reaching optimum athletic performance and promoting recovery. This review will scope the current literature in relation to nutritional knowledge and dietary intake of athletes in order to establish gaps in the research that require further exploration.